GUIDELINES FOR PRESERVING ANCIENT SITES WAT PHRAPHUTTHABATH RATCHAWORAMAHAWIHARN SARABURI PROVINCE - Chaithammapat, Phra Thornthanat (Journal of Buddhist Innovation Review, 2023)
This research study focuses on these three objectives: 1) to study the history of the ancient site of Wat Phra phutthabath Ratchaworamahaviharn in Saraburi Province 2) to study the value, importance, and benefits of the ancient site of Wat Phraphutthabath Ratchaworamahaviharn in Saraburi Province 3) to present guidelines for preserving the ancient site Wat Phraphutthabath Ratchaworamahaviharn in Saraburi Province in order to enhance the value and benefits to Thai society This study is a qualitative study (fieldwork) using methodology of In-depth interview of 12 key informants and analyzing to synthesize the data with descriptive analysis. The research results showed that the history of the ancient sites, Wat Phraphutthabath Ratchaworamahaviharn in Saraburi Province, which is the highest type of first class monastery consisting sources of antiquities represent the emergence of stories as well as way of life and culture of various eras in the past until the present. These are important for both historical and archaeological benefits therefore antiquities are important elements that coexist with religious sites. Wat Phraphutthabath Ratchaworamahaviharn is one of the significant temples with a large number of artifacts obtained from Buddhist offerings, from monarchs to commoners. The value, importance, and benefits of the ancient site of Wat Phraphutthabath Ratchaworamahaviharn in Saraburi Province have developed religious sites, religious artifacts, and environment inside the temple to be clean, shady, with admirable landscape. They have also cultivated personnel to have modern knowledge both secular and moral and have improved activities within the temple. Archaeological sites and artifacts are classified as part of "cultural heritage" that cover various types of resources in both tangible and intangible culture, and represent as the inheritance of humanity. The development of various facilities attracting the minds of many people to believe in Buddhism in order to continually nurture it. For guidelines for preserving the ancient site Wat Phraphutthabath Ratchaworamahaviharn in Saraburi Province, are showed as preservation steps respectively: 1) study and collect primary data of history, archeology evidence, architectures, fine arts, and other related aspects 2) basic preservation which can be proceeded in the following steps: (1) maintenance (2) protection (3) security enhancement (4) the use of ancient sites 3) advanced preservation that must be carried out in various stages under the recommendations of the Fine Arts Department only, namely,: (1) prevention of deterioration (2) replication (3) restoration (4) renovation (5) reassembly (6) functional application.